2019
DOI: 10.11622/smedj.2019017
|View full text |Cite
|
Sign up to set email alerts
|

Review of magnetic resonance imaging features of complications after anterior cruciate ligament reconstruction

Abstract: The goal of anterior cruciate ligament (ACL) reconstruction is to restore knee function that is identical to that of the native ligament and prevent long-term irreversible damage. ACL reconstruction remains the gold standard of care, particularly in active patients in whom non-operative management has been shown to result in poorer functional outcome. (1) The timing of surgery and type of graft utilised continue to be the subject of debate. For most patients, early reconstruction (within 21 days) is preferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…This situation may lead to contact or friction between the graft and the roof of the intercondylar notch. 17,18 Suboptimal tunnel positioning on MRI or radiography does not always lead to clinical problems. Therefore, considering the clinical features of patients who have undergone ACL reconstruction is essential when evaluating suboptimal tunnel positioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation may lead to contact or friction between the graft and the roof of the intercondylar notch. 17,18 Suboptimal tunnel positioning on MRI or radiography does not always lead to clinical problems. Therefore, considering the clinical features of patients who have undergone ACL reconstruction is essential when evaluating suboptimal tunnel positioning.…”
Section: Discussionmentioning
confidence: 99%
“…This situation may lead to contact or friction between the graft and the roof of the intercondylar notch. 17 18…”
Section: Discussionmentioning
confidence: 99%
“…There are two main reasons for reoperation after ACL-R: knee laxity and reduced mobility [22]. The most common indications for reoperations after ACL-R are meniscal surgery, arthrofibrotic tissue removal, notch plasty and ACL revision [12].…”
Section: Introductionmentioning
confidence: 99%
“…The hard part of the lesion consists of bone and cartilage tissue and causes symptoms more often than the softer cycloptic scar tissue [3]. A cyclops lesion is localised in the notch between the medial and lateral femoral condyles and in front of the reconstructed ACL [6,17,22]. A systematic review reported the incidence of arthroscopic removal of cyclops lesions to be 1.9%-10.2% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding regeneration of the graft, magnetic resonance imaging (MRI) evaluation, which lacks arthroscopic evaluation, is still needed. Although MRI is valuable postoperatively to assess graft healing and maturation (11), the integration, tension, and synovial membrane covering of the graft are still di cult to evaluate. As a second-look arthroscopic study is not ethically defensible, there is a lack of literature focused on the correlation between the clinical outcome and arthroscopic evaluation of the graft after reconstruction.…”
Section: Introductionmentioning
confidence: 99%